Note on a Cresset found near Hawick (Proceedings of the Society of Antiquaries of Scotland, 1918)
The cresset is a block of stone roughly squared, and bearing on one face circular cups disposed like the pips of a five of hearts. The rock-garden in which it was discovered is largely composed of fragments of dressed and carved stone'”the remains of window-sills, capitals of pillars, and ornamental mouldings. These fragments are known to have come from the old church of Hassendean, which used to stand not more than 300 yards away. As regards its use, the only probable suggestion that has been made is that it was a lamp-stand of that primitive kind which is properly known as a " cresset."